2008
DOI: 10.1186/1472-6831-8-19
|View full text |Cite
|
Sign up to set email alerts
|

Oral maxillofacial neoplasms in an East African population a 10 year retrospective study of 1863 cases using histopathological reports

Abstract: Background: Neoplasms of the oral maxillofacial area are an interesting entity characterized by differences in nomenclature and classification at different centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
21
2
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
10
21
2
1
Order By: Relevance
“…39,40 While the gender distribution of Burkitt's lymphoma is in support of published reports, 3,9 the observed slight predilection for the maxilla contrasts with other reports that noted higher occurrence in the mandible. 3,9,14 The results of this study support the observed female predominance for rhabdomyosarcoma 5 but differs from that of a study from Germany. 41 Other malignant jaw tumors such as Hodgkin and nonHodgkin lymphomas, malignant salivary gland tumors, neural and vascular lesions were not observed in this series.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…39,40 While the gender distribution of Burkitt's lymphoma is in support of published reports, 3,9 the observed slight predilection for the maxilla contrasts with other reports that noted higher occurrence in the mandible. 3,9,14 The results of this study support the observed female predominance for rhabdomyosarcoma 5 but differs from that of a study from Germany. 41 Other malignant jaw tumors such as Hodgkin and nonHodgkin lymphomas, malignant salivary gland tumors, neural and vascular lesions were not observed in this series.…”
Section: Discussioncontrasting
confidence: 79%
“…The reason for this difference may be explained by the exclusion of cystic and reactive lesions from the previous studies. 2,[12][13][14] Generally, studies from the developed countries reports higher proportion of malignant jaw lesions than benign lesions when compared to reports from Africa. This observed difference may be explained in terms of relatively lower life expectancy among Africans compared to their Western counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…This is evident in the fact that in our 12-year audit, not a single case was reported in this study, neither has it been reported across the African continent [31]. However, in China it is reported as the 2nd most frequent tumor type after PSA [15,31]. Eveson and Cawson found peak incidence of benign tumours in the 6th decade and malignant in the 7th decade.…”
Section: Sgt Histopathologymentioning
confidence: 50%
“…Warthin's tumour is rare in the black African population [6,8,[25][26][27][28][29][30][31]. Studies from Congo (Zaire), Nigeria, Malawi, South Africa, Kenya, Egypt and Uganda have recorded an almost equal involvement of the parotid, submandibular and minor salivary glands [6,24,[26][27][28][29][30].…”
Section: Salivary Gland Typementioning
confidence: 99%
“…El tratamiento de elección es la cirugía, con reportes de evolución favorable, aunque puede recidivar por exéresis incompleta 7 . La edad de aparición está entre los 30 y los 60 años 8,9 ; algunos autores sugieren que se diagnostica en la raza negra con mayor frecuencia, y sus dimensiones varían entre 0,3 y 10 cm 10 . El trauma puede aparecer como antecedentes personales, y se han publicado casos en familiares que sugieren una herencia autosómica dominante 11 .…”
Section: Introductionunclassified